Self-management open online trials in health [SMOOTH] an analysis of existing online trials [Protocol] - Price, A; Burls, A; Vasanthan, L; Clarke, M; Liew, S; Brice, A (PeerJ, 2016)

(untitled)
Background: The use of public engagement and self-management in online clinical trials is growing with benefits, boundaries and minimal methodological guidance. This analysis explores whether running self-recruited online trials can provide trustworthy and useful answers to research questions. Aim: To systematically explore existing self-recruited online randomized controlled trials of self-management interventions and analyze the trials to assess their strengths and weaknesses, the quality of trials reporting and to report how participants were involved in the research process. Methods: The O nline R andomized C ontrolled Trials of H ealth I nformation D atabase (ORCHID) will be used as a sampling framework to identify a subset of self-management self-recruited interventions. The trials will be used to explore the qualities of self-recruited online randomized controlled trials and to evaluate how useful they are for obtaining trustworthy answers to questions about health self-management and citizen research involvement. This research employs participatory action research where researchers and participants work as collaborators. Summary: This analysis can provide an overall view of effective methods for online trials and to provide insights into integration for online trials development as early as the protocol planning stage.